Aplikasi Ticket System untuk Engineering Test Service (ETS) pada PT. Honeywell Aerospace Indonesia - Omri Nainggolan; Muhammad Faizal; Muhammad Saleh (LPPM Sekolah Tinggi Teknologi Indonesia Tanjung Pinang, 2017)
The Engineering Test Service Activity management system in the company that is carried out is still not structured and with manual processes it will cause Ticket and Repair data storage systems as well as Preventive Maintenance and Calibration data, as well as data search and manufacture are very time consuming. This of course will be very detrimental to the company because it will have an impact on production output so that it does not satisfy all foreign companies that are customers of PT. Honeywell Aerospace Indonesia, which is a company engaged in the electronics sector for the manufacture of aircraft navigation instruments. This research is intended to build an application program that is most popular and popular to speed up the implementation of a process. The application program used is built with a structured input method and also automatically exists and only prints when needed. The Engineering Test Service (ETS) Activity management application can provide good results in processing the required data. The software used by the author as a tool in this study is the Visual Basic Access Database Program Application. The final result of the research is in the form of an application program that can process data and present data instantly with just a click with the menu form one for all (one for all).